SYSTEMATIZATION OF DESIGN AND OPERATIONAL PARAMETERS OF DISC-PAD BRAKES - Kindrachuk, Myroslav; Volchenko, Dmytro; Zhuravlov, Dmytro; Vudvud, Oleksandr; Vozniy, Andriy; Vasylyshyn, Vitaliy; Kharchenko, Volodymyr; Tkachenko, Natalia (Problems of Friction and Wear, 2025)
Conducted research on the construction of multi- and single-disc braking devices with their friction elements, as well as the determination of the main design and operational parameters in the case of local frictional interaction of friction pairs, made it possible to obtain the following: systematization, presenting it in the form of a graphic drawing with types of cooling; clarify the terminology related to the impulse normal force and specific load acting on the microprotrusions of the friction pairs; to recommend using the terminology average braking torque of friction pairs, since its definition is dependent on the average radius of the disc friction belt; the definition of the actual contact area should be represented as the sum of local contacts of microprotrusions of friction pairs; the role of influence of surface-bulk temperature gradients on deformations equivalent to stress is highlighted, taking into account methods of their effective reduction.